Pengawal Kelajuan Motor Arus Terus (AT) Dengan Menggunakan Mikropengawal PIC16F877 - Ismail, Nurashikin (Universiti Sains Malaysia, 2006)
The purpose of the project ‘Precision Speed Control of a DC Motor Using Microcontroller PIC16F877’ is to develop a system that can control speed of a direct current (DC) motor by using a microcontroller type PIC16F877. The technique that is used in this control system is called as Pulse Width Modulation, PWM. In this project, PWM is controlled by the programming language which is already programmed into the PIC16F877. Generally, this project is divided into two main sub-groups that provide the control program into the microcontroller and also by design a motor drive circuit and a feedback circuit. In the control program for motor, software called PicBasic Pro Compiler is used to control operation of the processor. Then in designing a motor drive circuit, it is involved the consumption of an H-Bridge circuit to receive output from the microcontroller and then drive the direct current motor to rotate. Since this project design is a closed-loop control system, a photo detector circuit is build to get the output pulse as a feedback input to the microcontroller. Programming the microcontroller and design the circuit that is needed in this project, is done periodically in order to confirm that all the combination circuits could communicate and operate well. This motor control application could be use as a basis in a robot control system and also for kids toys.